Anthropometric measurements associated with intertrochanteric fractures in the elderly: a case-control study (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Femoral intertrochanteric fracture is an important cause of disability in the elderly. Low muscle mass, especially those of the lower limbs, has been associated with osteoporosis and higher fall incidents. This study was aimed to assess the association between the anthropometric indices and intertrochanteric fractures. METHODS This case-control study was performed from September 2013 to July 2015. The criteria of case group were elderly patients with intertrochanteric fractures admitted in Dr. Sardjito Hospital within 72 hours after a low energy injury without multiple fractures or pathological fracture. For control group, the subjects were matched according to age and gender without any fracture. Thigh and calf circumferences were done on healthy limbs. Body mass index (BMI) was calculated. History of steroid use was obtained. Adjusted odds ratio (OR) was calculated using logistic regression after analyzed with student's t-test or chi-square test. RESULTS There were 82 subjects on each group. Smaller thigh and calf circumferences and also lower BMI were risk factors of intertrochanteric fractures. Thigh circumference <39 cm (aOR 5.12; 95% CI 2.30–11.43; p < 0.001) and calf circumference <29 cm (aOR 9.42; 95% CI 4.14–21.40; p < 0.001) were independently associated with intertrochanteric fracture after adjustment of BMI and steroid use. CONCLUSIONS Calf and thigh circumferences were independently associated with femoral intertrochanteric fractures in Indonesian elderly.